Temperature requirements, estimate of the generations number of Stenoma catenifer and verification of the model in the field - Nava, Dori Edson; Haddad, Marinéia de Lara; Parra, José Roberto Postali (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to study the biology of Stenoma catenifer under different temperatures, determine its temperature requirements, estimate the number of generations for the city of São Tomás de Aquino, MG, and verify the model in the field. In order to determine duration, viability, fecundity, longevity, and temperature requirements, the insects were reared on cultivar Breda avocado seeds at different temperatures, under 70±10% relative humidity and a 14-hour photophase. Developmental stages and biological cycle (egg-adult) durations were affected by temperature, with higher values at lower temperatures, while viability was highest at temperature ranging from 18oC to 28oC. The lowest temperature development threshold (Tb), and thermal constant (K) for the egg, caterpillar, and pupal stages, and for the egg-adult period were 9.1ºC and 82.3 GD, 8.3ºC and 398.4 GD, 10.1ºC and 164.7 GD, and 8.9ºC and 644.5 GD, respectively. Temperature influenced the egg-laying capacity and longevity of females and males. Based on the normal values of temperature, the numbers of generations per year and per production cycle were 7.8 and 5.1, respectively. The population fluctuation of S. catenifer can be used as an indicator of the number of generations, based on temperature requirements of the pest.
Keywords: Insecta; Lepidoptera; Elachistidae; avocado fruit borer; avocado